Application numerical wave channel study of wave and detached breakwater interaction in Ba Lang beach, Nha Trang coast - N., Viet Thanh (2020)
This paper presents the investigation of the wave and submerged breakwater interaction in Ba Lang beach, Nha Trang coast, Vietnam, using the numerical wave channel. The research results showed that the numerical wave channel had good capability in conducting numerical experiments with high nonlinearity of waves including the wave breaking and wave overtopping processes. In addition, the results also indicated that the structure of wave currents under wave motion was very complicated, especially the area around the breakwater. The effect of wave reduction depends on the free board height and a breakwater with free board height equal zero could be reduced 56.35% of wave height.